2022
DOI: 10.2519/jospt.2022.10952
|View full text |Cite
|
Sign up to set email alerts
|

2022 Bern Consensus Statement on Shoulder Injury Prevention, Rehabilitation, and Return to Sport for Athletes at All Participation Levels

Abstract: Professional and amateur athletes alike are burdened by shoulder injuries. 7,44,48,49,78,88 Shoulder pain affects athlete performance, training, and daily life. 61,64 More than half of elite collegiate American football players sustain at least 1 shoulder injury during their career. 48 Shoulder injuries are a problem for athletes in sports as diverse as rugby, 54 baseball, 34 handball, 20 diving, 73 water polo, 73 and kayaking. 41 Yet, there is a lack of quality evidence to guide clinicians, athletes, and coac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 98 publications
(113 reference statements)
2
43
0
Order By: Relevance
“…Despite few identified studies of moderate evidence quality, the effect sizes are comparable to other body regions 62. Our findings provide preliminary data to support the implementation of shoulder prevention programmes—in line with the recommendations from a recent consensus statement which concluded that ‘injury prevention programmes/exercises are appropriate to prescribe for athletes of all levels to prevent shoulder injury’ 8. However, three studies of low quality showed no preventative effect of exercise-based interventions, suggesting that investigations into differences in effects of exercise intervention characteristics (ie, frequency, type, dose, volume) is necessary to guide clinical practice.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Despite few identified studies of moderate evidence quality, the effect sizes are comparable to other body regions 62. Our findings provide preliminary data to support the implementation of shoulder prevention programmes—in line with the recommendations from a recent consensus statement which concluded that ‘injury prevention programmes/exercises are appropriate to prescribe for athletes of all levels to prevent shoulder injury’ 8. However, three studies of low quality showed no preventative effect of exercise-based interventions, suggesting that investigations into differences in effects of exercise intervention characteristics (ie, frequency, type, dose, volume) is necessary to guide clinical practice.…”
Section: Discussionsupporting
confidence: 82%
“…However, three studies of low quality showed no preventative effect of exercise-based interventions, suggesting that investigations into differences in effects of exercise intervention characteristics (ie, frequency, type, dose, volume) is necessary to guide clinical practice. Further, we recognise that effective shoulder injury prevention programmes do not always directly elicit improvements in modifiable risk factors60 (eg, glenohumeral internal rotation deficit, muscular imbalances, or scapula dyskinesis),5 6 and that exercise progressions1 44 and exercises individualised to sports-specific movements throughout the whole range of motion may be preferable 1 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite potential strengths, the present study shows certain limitations. Based on the fact that SP is multifactorial, several modifiable risk factors have been proposed in addition to limited rotation ROM, such as asymmetric ROM, rotational strength imbalance, weakness of the external rotators, altered scapular kinematics or load changes depending on the technical gesture [ 63 ]. The ratio between eccentric antagonist and concentric agonist strength is important when analysing shoulder symptoms experienced by badminton players [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder pain is one of the most common musculoskeletal complaints and can be extremely debilitating [ 47 ] for athletes in overhead sports [ 41 ]. In these sports, the shoulder joint is at high risk for overuse injuries due to their similar load and risk profiles [ 10 , 15 , 27 , 38 ].…”
Section: Introductionmentioning
confidence: 99%